The Portable Antiquities of the Netherlands: A Review. Issue 3 (August 2022) - Carpentier, Frank
Overview: The Portable Antiquities of the Netherlands (PAN) is an online system aimed at recording and documenting archaeological finds by the public. Since PAN launched in 2016, it has become an important data contributor to Dutch archaeology, amassing over 100, 000 recorded finds. These data, mostly the result of metal detection, enable scholars to gain new insights and policy makers to make more informed decisions. This review describes the context in which PAN was established, along with its current structure and scope, before looking at its different components, including the underlying database and linked data reference collection. In a final section, the article briefly addresses some common issues inherent to public reporting programs and how PAN approaches these issues.